Penggunaan Model Simulasi untuk Evaluasi Waktu Tunggu Penumpang dan Kapasitas Halte Trans Jogja - , YOGA ADIYASA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Trans Jogja is a part of Bus Rapid Transit (BRT) programmes initiated by The Ministry of Transportation. It needs the evaluation on its performance in order to attract the public. The evaluation are done to the time spent by the passengers in waiting the bus and to the capacity of Trans-Jogja bus stop which may affect the comfort of the passengers. From the results of the evaluation, it can be known whether there is unsuitability with the standardization or not. The evaluation is conducted by performing particular simulation model that serves as the representation of the actual incidents. This simulation model is used by involving random numbers with particular distribution, exponential and uniform distribution, based on the characteristics of data. Then, these simulation data must undergo verification and validity test in order to observe that data from the simulation greatly differ from those of survey. Scenarios are made to measure the minimum optimalisation of Trans Jogjaâs performance such as a plan to add the number of buses for particular destination and expand the bus stop. The chosen scenario is the scenario about the addition of the number of buses for particular destination. The expansion of bus stop is not good solution because of the limit of the space availability. Simulation model is expected to be helpful as the alternatives in the process of decision making of Trans Jogja âs performance managerial team.